Developing an undue influence screening tool for Adult Protective Services. Issue 2 (27th May 2017) - Quinn, Mary Joy; Nerenberg, Lisa; Navarro, Adria E.; Wilber, Kathleen H.
ABSTRACT: The study purpose was to develop and pilot an undue influence screening tool for California's Adult Protective Services (APS) personnel based on the definition of undue influence enacted into California law January 1, 2014. Methods included four focus groups with APS providers ( n = 33), piloting the preliminary tool by APS personnel ( n = 15), and interviews with four elder abuse experts and two APS administrators. Social service literature—including existing undue influence models—was reviewed, as were existing screening and assessment tools. Using the information from these various sources, the California Undue Influence Screening Tool (CUIST) was developed. It can be applied to APS cases and potentially adapted for use by other professionals and for use in other states. Implementation of the tool into APS practice, policy, procedures, and training of personnel will depend on the initiative of APS management. Future work will need to address the reliability and validity of CUIST.